Haemoglobin and Serum Ferritin Levels in Newborn Babies Born to Anaemic Iranian Women: a Cross-Sectional Study in an Iranian Hospital - Hadipour, Reihaneh; Norimah, A.K.; Poh, B.K.; Firoozehchian, F.; Hadipour, Raheleh; Akaberi, A. (Pakistan Journal of Nutrition, 2010)
The purpose of this study was to assess the haemoglobin and serum ferritin levels in newborn babies of anaemic mothers and to determine relationship between maternal iron status with neonatal biochemical and anthropometric characteristics. A total of 70 pregnant women aged between 17 and 40 years were divided into two groups based on their pre-delivery Haemoglobin (Hb) and Serum Ferritin (SF) concentrations; anaemic mothers Hb 10 ng/ml; normal control group Hb > 11 g/dl and SF > 10 ng/ml. Maternal biochemical assessments were obtained before delivery and neonatal anthropometric and biochemical measurements were obtained immediately after delivery. Mean maternal haemoglobin and serum ferritin levels were 11.2±1.16 (g/dl) and 45.8±20.8 (ng/ml), respectively. Incidence of anaemia among Iranian pregnant women in this study was 51.4%. Mean neonatal weight, length and head circumference born to anaemic mothers was 2.8±0.23 kg, 47.9±1.0 cm and 31.5±0.9 cm, respectively, while, among neonates born to normal mothers were 3.3±0.1 kg, 49.6±0.8 cm and 33.7±0.6 cm, respectively. No significant correlation were found between neonatal and maternal serum ferritin concentration. Significant differences were found between neonatal haemoglobin levels from normal and anaemic mothers (p